Expression of PTEN protein in prostatic adenocarcinoma - Duong, Thanh Tu; Pham, Quoc Thang; Nguyen, Tan Buu; Ly, Thanh Thien; Nguyen, Ngoc Minh Tam; Ngo, Quoc Dat (Tạp chí Y Dược Huế, 2024)
Background: PTEN protein is a new biomarker for identifying poor prognosis in prostatic adenocarcinoma. Objective: To evaluate the expression of PTEN protein in prostatic adenocarcinoma and assess the correlation between expression of PTEN protein with other clinicopathological characteristics in prostatic adenocarcinoma. Materials and methods: A descriptive analysis of 121 radical prostatectomy specimens diagnosed with prostatic adenocarcinoma at Binh Dan Hospital from January 2022 to December 2023. Interpret H&E and PTEN immunohistochemistry (IHC) slides. Analyse data and the correlation between clinicopathological and PTEN expression variables. Results: 72.7% of cases showed intact PTEN protein by IHC, while the rates of homogeneous and heterogeneous PTEN loss were 14.1% and 13.2%, respectively. Conclusion: Expression of PTEN protein was significantly associated with the 2019 International Society of Urological Pathology (ISUP) grade groups; however, there was no significant correlation between PTEN expression and other clinicopathological characteristics